2019
DOI: 10.1111/conl.12683
|View full text |Cite
|
Sign up to set email alerts
|

Alternative pathways to sustainable seafood

Abstract: Seafood certifications are a prominent tool being used to encourage sustainability in marine fisheries worldwide. However, questions about their efficacy remain the subject of ongoing debate. A main criticism is that they are not well suited for small‐scale fisheries or those in developing nations. This represents a dilemma because a significant share of global fishing activity occurs in these sectors. To overcome this shortcoming and others, a range of “fixes” have been implemented, including reduced payment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 36 publications
(47 reference statements)
2
29
0
Order By: Relevance
“…To date, ASNs have been described as an important strategy for small-and mid-size seafood operations to build firm-level resilience (Kittinger et al, 2015;Stoll et al, 2020). However, the relative shock-tolerance that ASNs exhibited during the COVID-19 pandemic also suggests that they may also contribute to the "systemic resilience" of the broader seafood economy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, ASNs have been described as an important strategy for small-and mid-size seafood operations to build firm-level resilience (Kittinger et al, 2015;Stoll et al, 2020). However, the relative shock-tolerance that ASNs exhibited during the COVID-19 pandemic also suggests that they may also contribute to the "systemic resilience" of the broader seafood economy.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, key distinctions between them exist in terms of their relationship and geographic orientation to consumers. In particular, what local and regional seafood systems lack in their overall geographic domain and market potential, they make up in their direct connection and proximity to consumers (Stoll et al, 2020). This "relational" orientation between harvesters and consumers sets local and regional seafood systems apart from their global counterparts.…”
Section: Alternative Seafood Network As a Source Of Systemic Resiliencementioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies have suggested that the implementation of monitoring, traceability and labeling programs could help to reduce mislabeling ( Ugochukwu et al, 2015 ; Marin et al, 2018 ; Willette & Cheng, 2018 ), our research suggests that while this would help in certain circumstances (e.g., species with high levels of supply) this alone would not solve the issue. Especially since value chain interventions, including certifications that mainly rely on economic incentives, risk not achieving the expected socio-ecological success at the ecosystem level and there is a need to work towards alternative pathways for seafood sustainability ( Kourantidou, Kaiser & Blasiak, 2019 ; Stoll, Bailey & Jonell, 2020 ). In addition, we suggest interventions that include communication efforts with stakeholders and educational campaigns of consumers ( Mariani et al, 2014 ), including actors along a relatively short value chain ( Fig.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…This is surprising given the rising number of FIPs as well as the existence of tools for transparently monitoring, evaluating and reporting FIP progress. This is also concerning because it means that the sector is increasingly advocating for the 'FIP model' which has yet to be shown to work across fisheries and contexts (Barr et al, 2019;Stoll et al, 2020). Therefore, more research is ur- Social network analysis is but one of the tools that can help better understand how social networks and social capital matter to FIP performance, but it could bring significant insights on the impact of social relationships and social capital for achieving successful collective outcomes.…”
Section: Future Re S E Archmentioning
confidence: 99%